Inside Cover: Novel Triazolopyrimidine‐Derived Cannabinoid Receptor 2 Agonists as Potential Treatment for Inflammatory Kidney Diseases (ChemMedChem 2/2016). Issue 2 (19th January 2016) - Nettekoven, Matthias; Adam, Jean‐Michel; Bendels, Stefanie; Bissantz, Catarina; Fingerle, Jürgen; Grether, Uwe; Grüner, Sabine; Guba, Wolfgang; Kimbara, Atsushi; Ottaviani, Giorgio; Püllmann, Bernd; Rogers‐Evans, Mark; et al.
Abstract : The inside cover picture shows a highly potent and selective triazolopyrimidine‐derived CB2 agonist in the consensus drug‐binding pocket of a CB2 homology model. The CB2 receptor belongs to the family of G‐protein coupled receptors (GPCRs) and plays a pivotal role in regulating inflammatory processes. This model helped guiding systematic structure–activity relationship (SAR) exploration to optimize for potency. In addition, we utilized this model to enhance the selectivity towards the CB1 receptor and to improve the physicochemical properties of the ligands. This yielded an in vivo active compound protecting rodent kidneys from inflammatory damage and fibrosis. More information can be found in the Communication by Matthias Nettekoven et al. onpage 179 in Issue 2, 2016 (DOI:10.1002/cmdc.201500218 ).